An infant of 26 weeks gestation with congenital miliary tuberculosis complicated by chronic lung disease requiring CPAP was diagnosed on Day 104 of life: congenital tuberculosis was confirmed by detection of calcified ovaries in his mother. (3rd April 2022) - Matsuda, Akina; Nishizaki, Naoto; Abe, Hanako; Mizutani, Akira; Niizuma, Takahiro; Obinata, Kaoru; Oguma, Kyoko; Makino, Shintaro; Ishitate, Makoto; Shimizu, Toshiaki
ABSTRACT: Introduction: Early diagnosis of tuberculosis (TB) in infants is important but is commonly missed because the symptoms are often non-specific. Case presentation: A Nepalese male infant born at 26 weeks gestation and weighing 1227 g (97th centile) was admitted to the neonatal intensive care unit (NICU) immediately after birth for the management of his prematurity. After extubation on Day 8, his oxygen saturation became unstable and he required nasal continuous positive airway pressure with oxygen for 3 months. On Day 104, further detailed evaluation was required because there was no improvement in his respiratory condition. A computed tomography (CT) scan demonstrated scattered miliary nodules in both lung fields. Acid-fast staining for the mycobacteria and TB polymerase chain reaction (PCR) of the sputum obtained directly by laryngeal aspiration confirmed Mycobacterium tuberculosis . On Day 105, he was therefore transferred to a tertiary care hospital for further intensive care. Pathology findings suggested placental involvement with TB owing to chronic endometrial infection. In addition, a maternal abdominal CT scan demonstrated bilateral calcified lesions in the ovaries. He completed antituberculous chemotherapy and was discharged 3 months later. At 18 months of age there are no sequelae and his development is almost normal. None of the infants or medical personnel who were exposed in the NICU developed secondary TB. Conclusion: In neonates with persistent respiratory distress, neonatologists should consider TB infection as a differential diagnosis. Abbreviations: CLD: chronic lung disease; CRP: C-reactive protein; CT: computed tomography; IGRA: interferon-γ release assay; IVF-ET: in vitro fertilisation-embryo transfer; N-CPAP: nasal continuous positive airway pressure; NICU: neonatal intensive care unit; PCR: polymerase chain reaction; PROM: premature rupture of membranes; TB: tuberculosis; WBC: white blood cells.